Read-through transcription of tRNA underlies the cell cycle-dependent dissociation of IHF from the DnaA-inactivating sequence datA - Kasho, Kazutoshi; Sakai, Ryuji; Ito, Kosuke; Nakagaki, Wataru; Satomura, Rion; Jinnouchi, Takafumi; Ozaki, Shogo; Katayama, Tsutomu (Frontiers in Microbiology, 2024)
Timely initiation of chromosomal DNA replication in Escherichia coli is achieved by cell cycle-coordinated regulation of the replication origin, oriC, and the replication initiator, ATP-DnaA. Cellular levels of ATP-DnaA increase and peak at the time for initiation at oriC, after which hydrolysis of DnaA-bound ATP causes those to fall, yielding initiation-inactive ADP-DnaA. This hydrolysis is facilitated by the chromosomal locus datA located downstream of the tRNA-Gly (glyV-X-Y) operon, which possesses a cluster of DnaA-binding sequences and a single binding site (IBS) for the DNA bending protein IHF (integration host factor). While IHF binding activates the datA function and is regulated to occur specifically at post-initiation time, the underlying regulatory mechanisms remain obscure. Here, we demonstrate that datA-IHF binding at pre-initiation time is down-regulated depending on the read-through transcription of datA IBS initiated at the glyV-X-Y promoter. During the cell cycle, the level of read-through transcription, but not promoter activity, fluctuated in a manner inversely related to datA-IHF binding. Transcription from the glyV-X-Y promoter was predominantly interrupted at datA IBS by IHF binding. The terminator/attenuator sequence of the glyV-X-Y operon, as well as DnaA binding within datA overall, contributed to attenuation of transcription upstream of datA IBS, preserving the timely fluctuation of read-through transcription. These findings provide a mechanistic insight of tRNA transcription-dependent datA-IHF regulation, in which an unidentified factor is additionally required for the timely datA-IHF dissociation, and support the significance of datA for controlling the cell cycle progression as a connecting hub of tRNA production and replication initiation.